Nobelova nagrada za fiziko 2016 - Žitko, Rok (Obzornik za matematiko in fiziko, 2017)
The Nobel prize in physics 2016 was awarded to three theoretical physicists who were the first to apply the concepts and tools from topology to demonstrate that different phases of matter may be distinguished not only by their symmetry properties, but also through their topological order. They have explained how there can be phase transitions without any symmetry breaking in two-dimensional systems hosting vortex excitations, how the quantized conductance in quantum Hall systems reflects the topology of the occupied states, and how differ spin chains with integer and half-integer spin.
Keywords: fazni prehodi; fizika; Nobelova nagrada; topološki red